Promoting Physical Activity and Reducing Sedentary Behaviors among French Adolescent Girls from Low-Incomes Communities - Virginie Nicaise; Guillaume Martinent; Bethania Rauseo; Emma Guillet-Descas (MDPI AG, 2021)
(1) Background: Despite health benefits of engaging in regular physical activity (PA), adolescents fail to achieve the recommended PA practice (especially among girls with low socio-economic position). Researchers have been prompted to adopt models of social cognition to help identify the role of psychological factors in influencing PA and sedentary behaviors. Thus, this study examined the effects of an intervention promoting PA, reducing sedentary activity among adolescent girls from low-incomes communities, and explored the relationships between core constructs of salient theoretical frameworks (self-determination theory, theory of planned behavior, implicit and explicit attitude towards PA, and sedentary behaviors); (2) Methods: An intervention was delivered to 28 adolescent girls. They reported their scores on a variety of core psychological constructs grounded within the aforementioned theoretical frameworks as well as on several outcomes, such as objective PA (pedometers) and perceived mental and physical health. These scores were gathered both before and after the 8-weeks program; (3) Results: Results revealed changes on external regulation and implicit attitudes toward sedentary behaviors from before to after the program. However, objective PA behavior did not change; (4) Conclusions: Future studies are encouraged to further explore mechanisms of behavior change derived from integrated and socio-ecological theories.